The Analisis Pemanfaatan Perpustakaan Sekolah Dalam Menumbuhkan Minat Membaca dan Keterampilan Membaca Siswa DI SDN Porisgaga 1 - Aqila Fadiya Haya; Erdhita Oktrifianty; Najib (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research discusses the learning process by utilizing the school library. By utilizing the school library, it becomes one of the important efforts in helping teachers to foster students' interest and reading skills. The purpose of this study is how the utilization of the school library at SDN Porisgaga 1. And how students' interest in reading and reading skills at SDN Porisgaga 1. The research method used in this research is descriptive qualitative method. The data collection techniques used were observation, interviews, questionnaires, and documentation. The questionnaire is intended to determine students' interest in reading and the questionnaire consists of 15 statements. Data analysis techniques in this study are data reduction, data presentation and drawing conclusions. The results showed that 1) The utilization of the school library has not been maximized. Because there are still some obstacles such as the lack of infrastructure and there is no significant increase in the number of visits and book borrowers in the library. 2) Students' interest in reading by utilizing the library, from the questionnaire results show quite good results, with an avarage of 84%. The highest percentage value of students is 100% and the lowest percentage is 60%. 3) Students' reading skills at SDN Porisgaga 1 are still low because from the data on student scores, there are still some who are not fluent in reading. In this case, the school library at SDN Porisgaga 1 needs an update by applying silent visual media to promote the library in maximizing literacy programs and activities in the school library so that students' interest and reading skills can increase.